Penerapan Pembelajaran Inquiry Terbimbing Untuk Meningkatkan Motivasi Dan Hasil Belajar IPA Pada Materi Gaya Dan Hukum Newton Terhadap Siswa SMP Negeri 2 Tanete Riaja Kabupaten Barru - Masniah Masniah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to determine the motivation and learning outcomes of class VIII-3 students who are taught by a guided inquiry learning model on the material of Newton's Law and style. This research is a classroom action research consisting of two cycles. Each cycle consists of four stages including planning, acting, observing, and reflecting. In this study, there are two types of variables studied, namely: problem variables, namely motivation and science learning outcomes, and action variables, namely the application of guided inquiry learning. The instrument used to measure in this study was a motivation questionnaire instrument and a test sheet. The data analysis used was descriptive statistics. The results of this study indicate that the application of Guided Inquiry learning can improve motivation and science learning outcomes in Newtonian force and law material for class VIII-3 students of SMP Negeri 2 Tanete Riaja.